2008
DOI: 10.1016/j.ceramint.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behaviour of ceramic bodies from contaminated marine sediments

Abstract: The effect of the heating temperature on the properties of sintered ceramic bodies from three different contaminated marine sediments was investigated. The sintering behaviour was evaluated by means of the variation of shrinkage degree, bulk density, water absorption, open and closed porosity, while the phases transformation were investigated by differential thermal analysis (DTA), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results have shown that the sintering process follows a viscou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 41 publications
1
39
0
2
Order By: Relevance
“…Tile 1 sintered to 1200˚C with the highest porosity of 31.32% also recorded the lowest bulk density of 1.82 g/cm 3 . Tile 3 sintered to 1200˚C with the lowest porosity of 11.29% recorded the highest bulk density of 2.01 g/cm 3 . Similar observations were observed for other samples though the bulk densities seem to remain constant as porosity increased.…”
Section: Apparent Porosity and Bulk Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Tile 1 sintered to 1200˚C with the highest porosity of 31.32% also recorded the lowest bulk density of 1.82 g/cm 3 . Tile 3 sintered to 1200˚C with the lowest porosity of 11.29% recorded the highest bulk density of 2.01 g/cm 3 . Similar observations were observed for other samples though the bulk densities seem to remain constant as porosity increased.…”
Section: Apparent Porosity and Bulk Densitymentioning
confidence: 99%
“…Figure 3 shows that water absorption of samples sintered to 1200˚C decreased with increasing steel slag addition down to 40 wt% before slightly increasing with further additions. Romero et al, 2008, suggested that closed porosity dominates at high [5], which stipulated 10% to 18% and 6% to 10% for wall tiles and floor tiles respectively. Water absorption requirements for floor tiles are much lower; therefore samples generated from this work could be suitable for floor tiles purposes.…”
Section: Water Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples sintered at 1190 o C were nearly impermeable. The occurrence of open porosity in the sintered samples could be favoured by different causes, such as entrapped air in the ceramic slurry, formation of voids during the different drying steps, gases released in the thermal decomposition of carbonates and sulphates or even liberation of gases dissolved in quartz particles [22]. As the sintering temperature increases, the capillary pressure due to the surface tension of the liquid phase tends to approach the particles, which in turn changes the porosity from open to closed porosity, which is formed by larger, isolated, spherical pores.…”
Section: Tests and Analysis Performed On The Raw Materials And The Cementioning
confidence: 99%
“…In this sense, the recovery of wastes currently generated in most industrial processes is the subject of a thorough investigation [1]. Wastes valorisation in building materials as secondary raw materials could allay the health and environment problems associated with both the depletion of natural resources and the disposal of industrial wastes [2], although the economic benefits accruing from waste recycling must not be ignored [3].…”
Section: Introductionmentioning
confidence: 99%